SKI-II – a sphingosine kinase 1 inhibitor – exacerbates atherosclerosis in low-density lipoprotein receptor-deficient (LDL-R−/−) mice on high cholesterol diet. Issue 1 (May 2015) - Potì, Francesco; Ceglarek, Uta; Burkhardt, Ralph; Simoni, Manuela; Nofer, Jerzy-Roch
Abstract Background Sphingosine 1-phosphate (S1P) is a lysosphingolipid associated with high-density lipoproteins (HDL) that contributes to their anti-atherogenic potential. We investigated whether a reduction in S1P plasma levels affects atherosclerosis in low-density lipoprotein receptor deficient (LDL-R−/−) mice. Methods and Results LDL-R−/− mice on Western diet containing low (0.25% w/w) or high (1.25% w/w) cholesterol were treated for 16 weeks with SKI-II, a sphingosine kinase 1 inhibitor that significantly reduced plasma S1P levels. SKI-II treatment increased atherosclerotic lesions in the thoracic aorta in mice on high but not low cholesterol diet. This compound did not affect body weight, blood cell counts and plasma total and HDL cholesterol, but decreased triglycerides. In addition, mice on high cholesterol diet receiving SKI-II showed elevated levels of tumor necrosis factor-α and endothelial adhesion molecules (sICAM-1, sVCAM-1). Conclusion Prolonged lowering of plasma S1P produces pro-atherogenic effects in LDL-R−/− mice that are evident under condition of pronounced hypercholesterolemia.